2020
DOI: 10.1080/10942912.2020.1828455
|View full text |Cite
|
Sign up to set email alerts
|

Sensory taste properties of chicken (Hy-Line brown) soup as prepared with five different parts of the chicken

Abstract: Taste is one of the main chicken soup characteristic quality factors as it affects palatability as well as consumer acceptability. Metabolomics coupled with sensory analysis method were applied to explore the differences of taste-chemical compositions in chicken carcasses and their correlation to the sensory qualities. Results showed that organic acid were the main taste compounds contained in the five kinds of chicken soup samples. The umami taste intensity of chicken breast meat soup was significantly higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 36 publications
5
26
0
Order By: Relevance
“…With the addition of ginger, the content of Glu and Asp in chicken soup increased significantly. The content of bitter amino acids in chicken soup and ginger chicken soup was the highest, which was consistent with the research of Zhang et al (2020) and may be caused by protein denaturation and secondary bond breaking during heating, which lead to the exposure of hydrophobic amino acids such as arginine [ 39 ].…”
Section: Resultssupporting
confidence: 88%
“…With the addition of ginger, the content of Glu and Asp in chicken soup increased significantly. The content of bitter amino acids in chicken soup and ginger chicken soup was the highest, which was consistent with the research of Zhang et al (2020) and may be caused by protein denaturation and secondary bond breaking during heating, which lead to the exposure of hydrophobic amino acids such as arginine [ 39 ].…”
Section: Resultssupporting
confidence: 88%
“…Among them, the taste threshold of acetate was the lowest (TC = 2,000 μM), followed by citrate (TC = 2,600 μM) and malate (TC = 3,700 μM). The contents of oxalic acid (TC = 5,600 μM), tartaric acid, formic acid (TC = 4,345 μM), a C4:0, butyric acid; C6:0, caproic acid; C8:0, caprylic acid; C10:0, capric acid; C11:0, undecanoic acid; C12:0, lauric acid; C13:0, tridecanoic acid; C14:0, myristic acid; C15:0, pentadecanoic acid; C16:0, palmitic acid; C17:0, margaric acid; C18:0, stearic acid; C21:0, heneicosanoic acid; C22:0, behenic acid; C24:0, lignoceric acid; C14:1, myristoleic acid; C16:1, palmitoleic acid; C17:1, heptadecenoic acid; C18:1 n-9t, vaccenic acid; C18:1 n-9c, oleic acid; C18:2, linoleic acid; C18:3, α-linolenic acid; C20:1, eicosenoic acid; C20:2, eicosadienoic acid; C20:3, eicosatrienoic acid; C20:4, arachidonic acid; C20:5, timnodonic acid TA B L E 1 (Continued) pyroglutamic acid (TC = 9,798 μM), and fumaric acid were also determined in chicken/chicken soup (Horio & Kawamura, 1990;Norris et al, 1984;Stark et al, 2006;Zhang et al, 2020). Presently, the sour-tasting peptides reported in chicken or chicken soup include VE (TC = 8,121 μM), WVNEEDHL, NSLEGEFKG, and KDLFDPVIQD (Kong et al, 2017;Zhang, Ma, et al, 2019).…”
Section: Sweet-tasting Compoundsmentioning
confidence: 99%
“…In the study reported by Aliani and Farmer, two phosphorylated (ribose‐5‐phosphate [R‐5‐P] and glucose‐6‐phosphate [G‐6‐P]) sugars were quantified, which showed that their content in breast meat was higher than that in leg meat (Aliani & Farmer, 2002 , 2005 ). Recently, two sweet‐tasting amino acid derivatives (sarcosine and β‐alanine) were studied in chicken (Hy‐line brown) soup (Zhang et al., 2020 ); however, the contribution of these two compounds to the sweetness of chicken soup is unclear due to the lack of data on their taste threshold. Alkaloid is a type of basic organic compound that contains nitrogen.…”
Section: Taste‐active Compounds In Chicken Soupmentioning
confidence: 99%
See 2 more Smart Citations